Pengaturan Fasilitas Penampungan Limbah Menurut Hukum Internasional Dan Implementasinya Dalam Penanganan Pencemaran Laut Di Indonesia - Putri Rebecca Simanjuntak; Idris; Nadia Astriani (Fakultas Hukum Universitas Gresik, 2023)
To anticipate that oil spills are not intentionally disposed of at sea, it is necessary to provide Reception Facilities at the port. Arrangements regarding the provision of Reception Facilities are expected to create sustainable development. This research is descriptive analytical, namely making systematic, factual and accurate predictions about the facts. Thus, this study will describe legal and factual issues related to the Provision of Reception Facilities in Indonesia, then analyze them in order to obtain a complete and comprehensive picture of the problems studied. With the policy of providing waste storage facilities at each port, it can be an effort to prevent environmental damage or pollution by planning carefully.